Comparative Analysis of Immunoinflammatory and Nutritional Measures in Surgically Resected Esophageal Cancer: A Single-center Retrospective Study - SAKAI, MAKOTO; SOHDA, MAKOTO; SAITO, HIDEYUKI; UBUKATA, YASUNARI; NAKAZAWA, NOBUHIRO; KURIYAMA, KENGO; HARA, KEIGO; SANO, AKIHIKO; OGATA, KYOICHI; YOKOBORI, TAKEHIKO; SHIRABE, KEN; SAEKI, HIROSHI (In Vivo, 2020)
Several immunoinflammatory and nutritional measures have been reported to be good prognostic indicators for esophageal cancer (EC). However, the association between those markers and the postoperative survival of EC patients remains unclear due to varying study designs and treatment strategies. The aim of this study was to compare the significance of preoperative immunoinflammatory and nutritional measures in patients with EC. One hundred and five patients with EC who underwent McKeown esophagectomy with gastric tube reconstruction without neoadjuvant therapy between 2006 and 2014 were included in this study. The prognostic values of preoperative modified Glasgow prognostic score (mGPS), controlling nutritional status (CONUT) score, prognostic nutritional index (PNI), C-reactive protein (CRP)-to-albumin ratio (CAR), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) were investigated using univariate and multivariate survival analyses. Multivariate analysis revealed that CAR and pathological stage are independent prognostic factors for overall survival (OS). CAR was significantly associated with more advanced pathological stage as both a subject and a continuous variable. Preoperative CAR was an independent prognostic factor for the OS of EC patients who underwent McKeown esophagectomy. The tumor-stage related increase in CAR demonstrated that a high CAR is associated with tumor progression in EC patients.